Web-Based Metacognitive Reflection to Develop Students’ Critical Thinking Skill: A Literature Review - Silvia Mariah Handayani; Sani Susanti; Nurlaila Nurlaila (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2026)
This study examines the contribution of web-based metacognitive reflection to the development of students’ critical thinking skills and the achievement of learning outcomes in higher education. A systematic literature review was conducted on 35 peer-reviewed studies published between 2015 and 2025 and retrieved from Scopus, Web of Science, ERIC, and Google Scholar. The review followed a structured process of identification, screening, eligibility assessment, and thematic synthesis. The findings indicate that web-based metacognitive reflection enhances critical thinking by promoting self-monitoring, self-evaluation, and reflective inquiry. Digital tools such as online journals, discussion forums, and e-portfolios provide opportunities for continuous reflection and feedback, leading to greater learner engagement and self-regulated learning. The reviewed studies consistently report positive effects on academic performance, conceptual understanding, and learner autonomy. Furthermore, students who participated in structured online reflective activities demonstrated stronger critical thinking abilities and improved achievement of learning outcomes compared with those in conventional learning environments. The review concludes that web-based metacognitive reflection is an effective pedagogical approach for fostering critical thinking and supporting learning achievement in higher education, particularly within technology-enhanced learning environments